The effectiveness of a proposed behavioral program on developing language skills for autistic children in elementary school age (Raparin Journal of Humanities (RJH), 2025)
The aim of this study is to construct a suggested behavioral program to development linguistic skills of autistic children, then identifying the effective of the program on autistic children whose age is between (6-8) to demonstrate the significant statistical differences between the pre-test and post-test in their linguistic skills, and identifying the value and huge in fact the program has on linguistic skills. In this study the researchers prepared a list of early childhood autism data (which contains information about the child) to gather information, for choose the study sample, and for sample homogeneity, and used Judard’s board to measure the cleverness (the board of shapes) and used Gilliam measurement (GARS-3) to identify autistic children, and for measurement of linguistic skills the researchers prepared a measure using literature and previous researches, which comprised of 25 items which were divided into two (Receipting language and expressive language). After extracting the specializations of the psychological measurement (validity and reliability), the measurement was ready. Then the researchers prepared a behavioral program to development linguistic skill (which is one of the skills of adaptive behavioral) of autistic children. After that they implemented the program on the sample of the study which was (8) children who were chosen after several regulatory action and consulting many experts. Using Wilcoxon-Test for the two correlated samples. The result was as follows: It was revealed that there is a significant statistical difference between the pre-test and post-test after implementing the program, and the impact of the program was noticeable. At the end based on the archived results suggestions and recommendation were presented.